Optimalisasi Bioherbisida Berbasis Limbah Kulit Jeruk Nipis (Citrus aurantifolia.) dengan Penambahan Effective Microorganisms (EM) sebagai Pengendalian Gulma pada Sektor Pertanian Padi - Muhammad Fardan Islam; Evan Fausta Subagya; Giesty Trienita; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2026)
This study aims to optimize bioherbicides based on lime peel waste (Citrus aurantifolia) supplemented with Effective Microorganisms (EM4) as an environmentally friendly alternative to synthetic herbicides in rice fields. This study utilizes natural phytotoxic compounds such as flavonoids, limonene, and tannins, which are enhanced through microbial fermentation. This study is descriptive with a qualitative comparative approach. The methods used include Soxhlet extraction with 96% ethanol, fermentation with EM4 concentrations of 0%, 3%, 5%, and 10%, and seven days of observation of organoleptic properties, soil pH, and weed toxicity. Data analysis compared changes in solution and weed response between treatments. Increased EM4 concentration resulted in a stronger odor, darker solution, and higher herbicide effectiveness; the 5% and 10% treatments caused total drying and collapse of weeds within 5–7 days, while 0% and 3% only caused mild chlorosis. Soil pH remained stable at 7, indicating no negative effects on soil fertility. Therefore, lime peel bioherbicide shows strong potential as an effective, inexpensive, and sustainable weed control option.